National Politics Study, 2008 - Jackson, James S. (James Sidney) ([Verlag nicht ermittelbar], 2015)
The 2008 election offers a rare opportunity to analyze a significant event in American history - the election of the first African American president. Because the longitudinal panel series began in 2004, prior to the emergence of President Obama as a serious political candidate and nominee, the results from these surveys provide a rare vehicle for comparing data over time on important demographic, political, and, of particular interest given President Obama's racial background, racial and ethnic issues related to vote choice and political behavior. The wealth of data obtained from this survey will benefit scholars for many years to come. This report provides a general overview of some of the key findings from the 2008 data collection. Topics covered include: demographic information of the population, work status, home ownership, political ideology, party identification, presidential choice, race relations, feeling thermometer data for a variety of political figures and relevant groups or organizations, and current events such as the Iraq War and same-sex marriage. Because differences among the racial and ethnic groups surveyed in this study are of political significance (Whites, African Americans, Hispanics, Asian Americans, and Caribbean Blacks), much of the data presented here is disaggregated by racial and ethnic group.